SOME COSINE OPERATOR FUNCTIONS IN R^3 - Vugdalić, Ramiz; Halilović, Sanela (Matematichki Bilten, 2025)
In this paper, we find out the cosine operator functions equation* C(t)= bmatrix a(t) & b(t) & c(t) 0 & d(t) & e(t) 0 & 0 & f(t) bmatrix equation* in a real vector space \(R^3 ( tR)\), as the solutions of the second order Cauchy problem equation* C’’(t)=A· C(t), C(0)=I, C’(0)=0. equation* We find the solutions for the various cases of a given real matrix equation* A= bmatrix A & B & C 0 & D & E 0 & 0 & F bmatrix, equation* which is a generator of these cosine operator functions \(C(t), tR\).